Evaluation of Bioequivalence of Two Long-Acting 20% Oxytetracycline Formulations in Pigs - Lei, Zhixin; Liu, Qianying; Yang, Bing; Ahmed, Saeed; Xiong, Jincheng; Song, Tingting; Chen, Pin; Cao, Jiyue; He, Qigai (Frontiers in Veterinary Science, 2017)
The aim of this study was to explore the bioequivalence of long-acting oxytetracycline in two formulations, a reference formulation (Terramycin 20% LA, Pfizer) and a test one (Kangtekang 20% LA, Huishen). Both formulations were administered intramuscularly at 20 mg/kg body weight at each of 24 healthy animals during a two-period crossover parallel experimental design. The oxytetracycline concentrations in plasma were measured by high-performance liquid chromatography (HPLC), and the limit of quantification was 0.05 μg/ml with a recovery ratio of above 90%. Moreover, the descriptive pharmacokinetics parameters (Cmax, AUC0-144h, AUC0-∞), were calculated and compared under analysis of variance and 90% confidence interval were compared, except for Tmax analyzed by non-parametric tests based on Wilcoxons’s signed rank test. The comparison results of Cmax, AUC0-144h, AUC0-∞, and Tmax, were 5.066 ± 0.486, 5.071 ± 0.877 μg/ml, 118.926 ± 13.259, 126.179 ± 17.390μg•h/ml, 123.087 ± 13.906, 130.732 ± 18.562 μg•h/ml, 0.740 ± 0.278, 0.650 ± 0.258 h, respectively, and did not reveal any significant differences. In addition, 90% confidence intervals of these ratios for reference and test product were within an interval of 80–125%, and the relative bioavailability of test one was (94.291 ± 15.287)%. Therefore, it has been concluded that test oxytetracycline was bioequivalent to the reference formulation in pigs.